Necroptosis mediates the antineoplastic effects of the soluble fraction of polysaccharide from red wine in Walker-256 tumor-bearing rats - Stipp, Maria Carolina; Bezerra, Iglesias de Lacerda; Corso, Claudia Rita; dos Reis Livero, Francislaine A.; Lomba, Luiz Alexandre; Caillot, Adriana Rute Cordeiro; Zampronio, Aleksander Roberto; Queiroz-Telles, José Ederaldo; Klassen, Giseli; Ramos, Edneia A.S.; Sassaki, Guilherme Lanzi; Acco, Alexandra (Carbohydrate polymers, 2017)
•Soluble fraction of polysaccharide extracted from cabernet franc wine has a complex mixture, with arabinogalactans, mannans and rhamnogalacturonans.•Soluble fraction of polysaccharide showed and expressive antineoplastic effects against the Walker-256 tumor in rats.•Soluble fraction of polysaccharide increased the tumor TNF-α production and activated the necroptosis pathway.•Soluble fraction of polysaccharide may be a potential therapy for cancers that are modulated by immune/inflammatory processes. Polysaccharides are substances that modify the biological response to several stressors. The present study investigated the antitumor activity of the soluble fraction of polysaccharides (SFP), extracted from cabernet franc red wine, in Walker-256 tumor-bearing rats. The monosaccharide composition had a complex mixture, suggesting the presence of arabinoglactans, mannans, and pectins. Treatment with SFP (30 and 60mg/kg, oral) for 14days significantly reduced the tumor weight and volume compared with controls. Treatment with 60mg/kg SFP reduced blood monocytes and neutrophils, reduced the tumor activity of N-acetylglucosaminidase, myeloperoxidase, and nitric oxide, increased blood lymphocytes, and increased the levels of tumor necrosis factor α (TNF-α) in tumor tissue. Treatment with SFP also induced the expression of the cell necroptosis-related genes Rip1 and Rip3. The antineoplastic effect of SFP appears to be attributable to its action on the immune system by controlling the tumor microenvironment and stimulating TNF-α production, which may trigger the necroptosis pathway.